STARATEGY OF COMMUNITY DISASTER PREPAREDNESS WITH COMMUNITY BASED DISASTER RISK MANAGEMENT (Case Study of Sukapada Village, Pagerageung District, Tasikmalaya Regency) - Atqiyani Setra, Risyda
Community preparedness is important for disaster risk management. Community-based disaster risk management (CBDRM) is an effort to reduce disaster risk by increasing the capacity of local communities by maximizing the potential and competency of the community. Active involvement and community participation in disaster risk management b is key, so that the approach is bottom-up because community independence is more dominant. The village of Sukapada, Kageratan Pagerageung is an area that is prone to land movement disasters, but only 3 (three) villages are affected by the land movement, namely Citereup Village, Garadaha Village, and Bojot Village which results in cracks on the road, and the walls or floor of the house. The potential of the local community in Sukapada Village is expected that the community can be independent and cooperate with the government in managing disaster risk, therefore the importance of building PRBBK in Sukapada Village. The purpose of this study is to formulate a community preparedness strategy for disasters through community-based risk management. In this study using qualitative methods with data collection methods using indepth interviews with the selection of informants conducted based on purposive sampling, field observations, documentation and secondary data to complete information. Then the data are analyzed descriptively qualitatively based on the CBDRR indicators, namely community preparedness, participation and resilience which are then analyzed by SWOT (Strengths, Weakness, Opportunity, Threats). The results of this study are that the people of Sukapada Village know that their area is prone to land movement disasters, the lack of community preparedness for disasters, the absence of special programs from the Sukapada Village Government on disasters and the unavailability of village funding for disasters. This research provides a strategy in the form of recommendations by looking at the potential and opportunities that can be developed by the government together with the local community.